Health Care of Vulnerable Populations Covered by Medicare and Medicaid - Hirsch, Marilyn B. (CENTERS for MEDICARE & MEDICAID SERVICES, 1994)
This overview discusses articles published in this issue of the Health Care Financing Review, entitled “Health Care Needs of Vulnerable Populations.” Articles cover the following vulnerable population subgroups: pregnant women and children, persons with AIDS, the disabled, and the elderly. Issues covered in this collection include: expenditures, demographic factors, Medicaid and Medicare policy, service use, medical procedures, and data collection.